Landscape connectivity in extensive livestock farming: an adaptive approach to the land sharing and land sparing dilemma - Pulido-Herrera, Luz Astrid; Sepulveda, Claudia; Jiménez, Jose Antonio; Betanzos Simon, Juan Eduardo; Pérez-Sánchez, Edwin; Niño, Larry (Frontiers in Sustainable Food Systems, 2024)
This study investigates the "land sharing" versus "land sparing" dilemma in the context of extensive cattle ranching in Chiapas, Mexico. Employing a comprehensive methodology that synthesizes various systems and uses a normalized matrix for relative priority assessment, we identified several geographic variables as zoning criteria. These criteria encompass the hemerobic index, proximity to structurally intact forests, fire frequency, and terrain slope, aiming to identify areas optimal for conservation. Our results highlight properties with high conservation potential and propose two distinct connectivity scenarios, both excluding currently preserved areas. The analysis focuses on the interplay between connectivity and hemeroby, identifying human-influenced regions within the landscape and emphasizing the importance of tree conservation in agricultural contexts for biodiversity preservation. By tackling the "land sharing" vs. "land sparing" debate, the study underscores the necessity of sustainable livestock practices and the critical role of connectivity in ranching landscapes for ecosystem preservation.